DIAGNOSTIC METHOD OF HIRSCPRUNG’S DISEASE - Trisnawan, I Putu; Darmajaya, I Made (E-Jurnal Medika Udayana, 2013)
Hirschsprung’s disease (congenital megacolon) is caused by the failed migration of colonic ganglion cells during gestation. Hirschsprung’s disease most commonly involves the rectosigmoid region of the colon but can affect the entire colon and, rarely, the small intestine. Symptoms in infants include difficult bowel movements, poor feeding, poor weight gain, and progressive abdominal distention. Early diagnosis is important to prevent complications (e.g., enterocolitis, colonic rupture). With proper treatment, most patients will not have long-term adverse effects and can live normally.
Keywords: hirschprung disease, aganglion